Dural based tumor causing cognitive decline: Answer. (February 2020) - Candanedo, Carlos; Kaye, Andrew H.; Moscovici, Samuel
Highlights: Primary dural lymphomas should be a differential diagnosis of dural based tumors. Complete removal should be achieved to improve overall survival. Primary dural lymphomas have better prognosis than other high grade lymphomas.